Beispiel Nr: 14
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 1 x +1 + 0 z=1\\ 1 x +0 y + 1 z=6\\ 0 x +1 y + -1 z=5\\ \\ \\ \textbf{Rechnung:} \\ 1 x + 1 y + 0 z=1\\ 1 x +0 y +1 z=6\\ 0 x +1 y -1 z=5\\ D_h=\left|\begin{array}{ccc} 1\ & 1 & 0\\ 1&0 & 1\\ 0& 1 & -1 \\ \end{array}\right| \begin{array}{cc} 1\ & 1 \\ 1&0 \\ 0& 1 \end{array} \\ D_h=1 \cdot 0 \cdot \left(-1\right)+1 \cdot 1 \cdot 0 +0 \cdot 1 \cdot 1 - 0 \cdot 0 \cdot 0 -1 \cdot 1 \cdot 1 -1 \cdot 1 \cdot \left(-1\right)=0 \\ D_x=\left|\begin{array}{ccc} 1\ & 1 & 0\\ 6&0 & 1\\ 5& 1 & -1 \\ \end{array}\right| \begin{array}{cc} 1\ & 1 \\ 6&0 \\ 5& 1 \end{array} \\ D_x=1 \cdot 0 \cdot \left(-1\right)+ 1 \cdot 1 \cdot 5 +0 \cdot 6 \cdot 1 - 0 \cdot 0 \cdot 5 - 1 \cdot 1 \cdot 1 -1 \cdot 6 \cdot \left(-1\right)=10\\ D_y=\left|\begin{array}{ccc} 1\ & 1 & 0\\ 1&6 & 1\\ 0& 5 & -1 \\ \end{array}\right| \begin{array}{cc} 1\ & 1 \\ 1&6 \\ 0& 5 \end{array} \\ D_y=1 \cdot 6 \cdot \left(-1\right)+1 \cdot 1 \cdot 0 +0 \cdot 1 \cdot 5 - 0 \cdot 6 \cdot 0 -1 \cdot 1 \cdot 5 -1 \cdot 1 \cdot \left(-1\right)=-10 \\ D_z=\left|\begin{array}{ccc} 1\ & 1 & 1\\ 1&0 & 6\\ 0& 1 & 5 \\ \end{array}\right| \begin{array}{cc} 1\ & 1 \\ 1&0 \\ 0& 1 \end{array} \\ D_z=1 \cdot 0 \cdot 5+1 \cdot 6 \cdot 0 +1 \cdot 1 \cdot 1 - 1 \cdot 0 \cdot 0 -1 \cdot 6 \cdot 1 -1 \cdot 1 \cdot 5=-10\\ \\ L=\{\}$